2022
DOI: 10.1097/yic.0000000000000416
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of suicidal ideation within acute phase treatment of major depressive disorder: analysis of clinical predictors

Abstract: Suicidal ideation (SI) is common in major depressive disorder (MDD), and it is a risk factor for suicidal behaviour. Antidepressants are effective in reducing SI, but in some subjects, SI may persist for weeks. This study aimed to disentangle the contribution of baseline clinical characteristics in SI nonremission at week 6. Research involved 198 outpatients with MDD and SI collected within the Combining Medications to Enhance Depression Outcomes trial and treated with different antidepressant combinations. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…In this context, one of the most popular approaches is to investigate and quantify suicide risk factors. Pompili (2022) has recently criticised this approach. In his opinion, the mere analysis of risk factors could be too simplistic and reductive as a preventive strategy for suicide.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, one of the most popular approaches is to investigate and quantify suicide risk factors. Pompili (2022) has recently criticised this approach. In his opinion, the mere analysis of risk factors could be too simplistic and reductive as a preventive strategy for suicide.…”
mentioning
confidence: 99%
“…Pompili (2022) provocatively argued against the common attitude of simply considering suicidal ideation a symptom of depression. This assumption would hinder a more comprehensive evaluation of patients with MDD experiencing suicidal ideation, including their past and recent traumatic experiences, stressful events, the presence of bipolar features, and current thoughts, emotions, and coping strategies that could contribute to suicidality (Olgiati et al, 2023, ICP – accepted for publication).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, a few predictors were associated with suicide risk, but they do not have a relevant predictive power (Fanelli et al , 2022; Li et al , 2022). Another issue is that a proper antidepressant treatment is not always effective in reducing suicidal ideation (Olgiati and Serretti, 2022) and a valid doctor-patient relationship may be the most valuable tool to predict and manage suicidal behaviors (Pompili, 2022). Lithium is one of the very few medications that consistently showed an antisuicidal effect (Del Matto et al , 2020).…”
mentioning
confidence: 99%
“…The study by Olgiati and Seretti (2022) is relevant to this discussion as it consistently emphasized how suicide ideation may persist in major depressive disorder patients despite treatment. These authors found that although suicidal ideation decreased from baseline to week 6, about 40% of the patients failed to achieve suicidal ideation remission.…”
mentioning
confidence: 99%